Do you know this syndrome? Heerfordt-Waldenström syndrome - Fraga, Rafael Cavanellas (An Bras Dermatol, 2017)
Heerfordt-Waldenström syndrome is a rare subacute variant of sarcoidosis, characterized by enlargement of the parotid or salivary glands, facial nerve paralysis and anterior uveitis. Granulomas with a peripheral lymphocyte deficit are found in the anatomic pathology of affected organs. It is normally self-limiting, with cure achieved between 12 and 36 months, but some prolonged cases have been reported. Diagnosis of the syndrome is clinical, and treatment depends on the degree of systemic impairment. Oral corticosteroids represent the first line treatment option. The mortality rate ranges between 1 and 5% of cases.